Supply chain management of retail food chain between warehouses and stores: a case study - Chocholáč, Jan; Kučera, Tomáš; Sommerauerová, Dana (Melandrium, 2017)
Supply chain management of the retail food chain is very unique, because network of the retail food chain is huge and there are many constraints for distribution of goods, for example time window of central warehouses and stores, distribution of perishable goods, more deliveries within the same day or distribution of objects of reverse logistics from stores to central warehouses. A lot of companies are using planning tools based on the subjective opinion now. This procedure is not enough effective. Article describes a diagram of the flows between stores and suppliers of one retail food chain in the Czech Republic which has almost 350 stores. All constraints which are connected with this issue and within the case study will the article present on the part of the distribution network of the retail food chain by the possibility of using selected algorithm of the graph theory – Vehicle Routing Problem with Time Windows.
Řízení dodavatelsko-odběratelského maloobchodního potravinářského řetězce mezi sklady a prodejnami: případová studie
Keywords: supply chain management; retail food chain; distribution; graph theory; vehicle routing problem with time windows; řízení dodavatelsko-odběratelského řetězce; maloobchodní potravinářský řetězec; distribuce; teorie grafů; úloha okružních jízd s časovými okny